Awareness of prostate cancer and its associated factors among male patients attending care in the urology unit at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Tilaye Gebru; Hussien Mekonnen; Negalign Getahun; Fentahun Meseret; Awoke Masrie; Mihiret Mandefro; Samrawit Shawel; Aklilu Tamire; Addisu Berhanu; Abdi Birhanu (BMJ Open)
Background Globally, prostate cancer is the most common cancer among men. It is the second most common cause of cancer-related deaths in men. Symptoms may be non-specific and may not present until the cancer has progressed. Raising awareness, knowing risk factors and symptoms and seeking early medical attention is critical for prevention and detection. The objective of this study is to assess the level of awareness of prostate cancer among male patients attending care in a urology unit in Ethiopia.Methods We conducted a cross-sectional study among 241 male patients at Tikur Anbessa Specialized Hospital from February to April 2021. Data were collected using an interviewer-administered questionnaire adapted from published studies and cancer awareness measurement tools. We used EpiData V.4.6.0 and SPSS V.26 for data entry and analysis. Descriptive statistics and linear regressions were used for analyses. Bivariate and multivariate linear regression analysis identified factors associated with prostate cancer awareness. Adjusted odd ratio (AOR) at 95% CI and p value<0.05 were considered statistically significant.Results A total of 250 patients were approached, and 241 (96.4%) responded. The mean scores for awareness of prostate cancer risk factors, symptoms, screening and prevention were 41.2%, 43.8%, 44.7% and 49.5%, respectively. Families with an average monthly income of more than 8900 ETB (Ethiopian birr), having heard about prostate cancer, having a regular source of care every six months or more, having a history of hospitalisation and having healthcare providers as the main source of information were all significantly associated with awareness of prostate cancer.Conclusion The findings of this study indicate that male patients have a relatively low level of awareness of prostate cancer risk factors, symptoms, screening and prevention. There should be more public awareness initiatives to educate men in Ethiopia on the risk factors, symptoms, screening and prevention of prostate cancer.